Islamic social finance waqf, endowment, and SMEs - Ismail, Shafinar; Hassan, M. Kabir 1963-; Rahmat, Suharni (Edward Elgar Publishing, 2023)
"Islamic Social Finance provides an introduction to the Waqf system, which has played a significant socio-economic role throughout the history of Islamic civilization. In a contemporary framework, Waqf creates new networks between micro-entrepreneurs, Small and Medium Sized Enterprises (SMEs), and entrepreneurship through voluntary donations made by individuals in a society. In other contexts, Waqf supports the financial system and contributes to the UN sustainable development goals (SDGs). The authors explore the relationship between the roles Waqf plays in realizing the SDGs, its contributions in many sectors of the economy, and the Waqf practices among the Southeast Asia countries, particularly Malaysia. They highlight the existing Waqf models and framework that have been used by many countries for entrepreneurship that can be used or adapted for the benefits of SMEs. This book is a comprehensive overview for academics, postgraduate students, entrepreneurs, and policy makers who wish to understand how Waqf can contribute to the economic progress of individuals and society at large"
Titel und Verantwortlichkeitsangabe der Landingpage (Elgaronline) entnommen, da kein Titelblatt vorhanden
Keywords: Finanzierung; Islam; Waḳf; Entwicklungspolitik